O COMPORTAMENTO DOS NÍVEIS ORGANIZACIONAIS NA ESCOLHA E IMPLEMENTAÇÃO DE FERRAMENTAS DE GESTÃO: O CASO MRS LOGÍSTICA - Moreira, Cleber Nassar (2005)
This paper intends to investigate the professionals' behavior of a transport company at the strategic, intermediary and operational levels, concerning about the decisions making process, support to implantation and imposition of obstacles for adopting management tools that are supporting the changes in course at the company. Presenting a vision of the behavior of the hierarchical levels face to the implemented changes, this paper contributes to the management body of the company to comprehend the logic of the implantation of management tools. The interested ones in knowing the changing process of a company that has faced a privatization process and the journey to adopt new administration tools found in this research a contribution. It was used in this research the case study method supported by documented researches and guided interviews through specific questionnaires to 144 professionals of operation level , 37 of intermediary level and 7 professionals of strategic level. The obtained results indicate that the strategic level has a strong participation to define such tools, offers strong support to use them and doesn´t impose any obstacles to their adoption ; the intermediary level has a weak participation to define such tools, offers some support to use them and doesn´t impose obstacles to their adoption; the operation level in general doesn't impose obstacles to use the proposed management tools and usually the company directors listen and give them freedom and support for suggestions and new ideas aiming to stimulate the creativity.